2019
DOI: 10.1051/0004-6361/201935781
|View full text |Cite
|
Sign up to set email alerts
|

Structure, kinematics, and ages of the young stellar populations in the Orion region

Abstract: We present a study of the three dimensional structure, kinematics, and age distribution of the Orion OB association, based on the second data release of the Gaia satellite (Gaia DR2). Our goal is to obtain a complete picture of the star formation history of the Orion complex and to relate our findings to theories of sequential and triggered star formation. We select the Orion population with simple photometric criteria, and we construct a three dimensional map in galactic Cartesian coordinates to study the phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 62 publications
7
96
0
Order By: Relevance
“…Using OmegaCAM photometry they identified three populations with an age difference of 3 Myr between the oldest and the youngest sequence. These sequences cannot be described with binary or triplet systems alone leading to the conclusion that they are real, which is in agreement with the above findings by Zari et al (2019) and suggesting star formation happens sequentially possibly triggered by the luminous OB stars.…”
Section: Observing Young Star-forming Regionssupporting
confidence: 89%
See 2 more Smart Citations
“…Using OmegaCAM photometry they identified three populations with an age difference of 3 Myr between the oldest and the youngest sequence. These sequences cannot be described with binary or triplet systems alone leading to the conclusion that they are real, which is in agreement with the above findings by Zari et al (2019) and suggesting star formation happens sequentially possibly triggered by the luminous OB stars.…”
Section: Observing Young Star-forming Regionssupporting
confidence: 89%
“…The ONC revealed the first direct imaging of protoplanetary disks (proplyds, McCaughrean and O'dell 1996;. A recent 3D kinematic study by Zari et al (2019) using Gaia DR2 data (Prusti et al 2016;Brown et al 2018) showed that the ONC is highly sub-structured, with stellar ensembles of different ages in several kinematic groups, mixed in 3D space, which are overlapping in projection. Jerabkova et al (2019) suggested that these YSCs may harbor multiple populations.…”
Section: Observing Young Star-forming Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kraus et al (2017) and Zhang et al (2018) also report on a distributed population of young stars in the Taurus region, which is older (>10 Myr) than the classical members of the region (Luhman 2018). Another wellknown example is the Orion complex, which is made up of sev-eral groups and clusters of YSOs with different ages (see Alves & Bouy 2012;Bouy et al 2014;Kounkel et al 2018;Zari et al 2019;Chen et al 2019). Our analysis conducted in this paper shows that Corona-Australis is one more such substructured starforming region that will require further investigation to understand its star formation history.…”
Section: Spatial Distribution Of Corona-australis Starsmentioning
confidence: 99%
“…The advent of the ESA Gaia satellite for the first time allows the study of young stellar populations on large scales (>100 pc) in six-dimensional (6D) position and velocity space. For example, using Gaia Data Release 2 (DR2) (Gaia Collaboration 2018a), Kounkel et al (2018) and Zari et al (2019) demonstrated that the Orion star-forming region is composed of a variety of populations with different spatial and kinematic properties each that are all likely generated in multiple events instead of in a progressive star formation history (see also Beccari et al 2017;Jerabkova et al 2019b;Kroupa et al 2018, discussing three bursts of star formation in the Orion Nebula cluster). Zari et al (2018) described the 6D properties and age structures in which young stars are found within a region of 500 pc around the Sun, and a number of other studies focusing on individual star-forming regions have been reported.…”
Section: Introductionmentioning
confidence: 99%